The effect of Thermo-oxidative aging on the mechanical properties and FTIR analysis of sugarcane fibre filled Polypropylene composite - Muhammad Arif Mat Saat (Universiti Malaysia Perlis, 2009)
The effect of thermo-oxidative aging for PP/Sugarcane composite with COCA or MAPP coupling agent and without coupling agent were investigated. The results indicated that the presence of coupling agent MAPP increased the interfacial adhesion between the fibers and the polymer matrix. New coupling agent, COCA showed slightly interaction between filler and matrix, when both of them were compared with PP/Sugarcane composite without coupling agent. Good interfacial adhesion was presented by mechanical properties, morphology and FTIR result. Overall thermooxidative aging showed, the composite degrade after exposed to the hot circulation temperature. Coupling agent MAPP required long time to degrade compared coupling agent COCA and without coupling agent. The degradation gave effect on the mechanical properties and morphology of the composite.